Structures et logiques du redéploiement de l’emploi métropolitain : le cas de l'aire métropolitaine de Montréal - Laurent Terral; Richard Shearmur (Territoire en Mouvement)
Employment in the Montréal agglomeration grew very rapidly between 1996 and 2001, and in this article we explore the intra-metropolitan spatial impact of this growth. By analyzing the evolving intra-metropolitan distribution of jobs at the census tract level, our contribution tries to show the different ways the employment distribution operates. We test two hypotheses : has it tended to concentrate in pre-existing centres, or has it increasingly tended to locate along major transport axes ?